2022
DOI: 10.3390/app12115597
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Capacity Assessment of the Selected Track Section on the Slovak Railways Network after the Implementation of ETCS L3 Based on Signaling Principle

Abstract: In the field of railway operation, it is essential to establish uniform conditions for interconnectivity requirements and compatibility of equipment in the Pan-European railway area to ensure effective interoperability. It also includes, for example, the introduction of a control system with modern and advanced interlocking systems (safety devices). The European Train Control System (ETCS) is a single European train protection system that will increase safety in rail transport. Nevertheless, this system may ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In the fourth deep learning level are combined at the input all the data from the first and second level of deep learning connected to the real infrastructure diagnostics data. It should be the learning from real failures and disorders and their traffic impact [9,10]. The output should be the prediction of failures (maintenance intervals, replacement requirements) with the impact to all three previous levels of deep learning.…”
Section: Resultsmentioning
confidence: 99%
“…In the fourth deep learning level are combined at the input all the data from the first and second level of deep learning connected to the real infrastructure diagnostics data. It should be the learning from real failures and disorders and their traffic impact [9,10]. The output should be the prediction of failures (maintenance intervals, replacement requirements) with the impact to all three previous levels of deep learning.…”
Section: Resultsmentioning
confidence: 99%
“…Van der Meulen developed a novel method to estimate moving block benefits that uses historic trajectory data from the existing fixed block control system, and used it to analyze various Dutch railway corridors ( 21 ). Dedik et al analytically compared ETCS Level 3 with existing automatic blocks and lower levels of ETCS on a section of the Slovak railway network, finding that ETCS Level 3 has the substantial capacity benefit of handling double the number of trains ( 22 ). Qian et al found that utilizing moving block increased the express passenger train capacity on the Qinghai-Tibet railway by 15% ( 23 ).…”
Section: Previous Researchmentioning
confidence: 99%